Rheumatic autoimmune disease in relation to post-traumatic stress disease and traumatic brain injury - Scofield, R. Hal; Lawrence, Stephanie; Kurien, Biji T.; Gross, Tim; Sorocco, Kristin; Prodan, Calin; Lewis, Valerie M. (Frontiers in Lupus, 2025)
BackgroundPost traumatic stress disorder (PTSD) is associated with traumatic brain injury (TBI) and autoimmune disease, including systemic lupus erythematosus (SLE). We sought to determine whether the association was related to only PTSD or the combination of PTSD and TBI.MethodsWe studied rheumatic disease autoantibodies in a cohort of 40 patients, 20 of whom had TBI without PTSD and 20 had both PTSD and TBI. None had diagnosed rheumatic autoimmune disease. We also examined a cohort of 229 TBI patients, of whom 60% had PTSD, for diagnosis of rheumatic autoimmune disease.ResultsAmong the 20 subjects with PTSD and TBI, 8 had autoantibodies [1 each with anti-Ro (or SSA), anti-RNP and anti-RNP plus anti-dsDNA, the remainder with a positive ANA]. Only 1 of 20 subjects with TBI alone had autoantibodies (p = 0.0088 by Fisher's Exact test). In the cohort of 229 subjects, there were 92 with TBI but no PTSD, of whom 4 (4.3%) had a diagnosed rheumatic autoimmune disease. Of the 137 with TBI and PTSD, 17 (13.3%) had an autoimmune rheumatic disease (p = 0.02 by Fisher's exact test).ConclusionWe found more autoantibodies in the sera of patients with TBI and PTSD than in TBI alone. In addition, we found a 3-fold increased prevalence of autoimmune rheumatic disease in patients with TBI and PTSD compared to those with TBI alone. TBI is strongly associated with PTSD but we conclude that TBI does not contribute to the increased risk of autoimmune disease in PTSD.